Identifying and Measuring Biophilic Planning Indicators in Riverside Neighborhoods - Abdulhussien Abdali Alaskary; Tuqa R. Alrobaee (Civil Engineering Journal, 2022)
Biophilic planning is one of the important trends in achieving sustainability and nature conservation, especially in areas that contain natural elements. Since in the case of climate change and urban encroachment on natural habitats, taking care of nature and investing its components properly is a necessity, not a choice. As well as the agreement among many researchers about the social, economic and environmental benefits provided by biophilic planning, which is based mainly on the idea of connecting people with nature. This study aims to provide a guide to planners, urban designers, and decision-makers, including how to deal with residential neighborhoods that contain natural elements such as rivers by depending on a specific methodology based on previous literature and deriving effective indicators in this type of neighborhood. The results of the theoretical framework showed that there are eleven effective indicators, some of which are measured by descriptive methods and some by quantitative methods. These indicators have been applied in one of the neighborhoods of the Iraqi Kufa City overlooking the Euphrates River. The results showed that the study area lacks standards and indicators of biophilic planning. Doi: 10.28991/CEJ-2022-08-01-03 Full Text: PDF